Specific depth cone resistivity measurements to determine soil engineering properties - Daniel, Chris R.; Campanella, R. G.; Howie, John A.; Giacheti, Heraldo L. [UNESP] (My University, 2003)
The University of British Columbia (UBC) began performing piezocone penetration tests (CPTU) with electrical resistivity measurements (RCPTU) in 1989. Since then, RCPTU research at UBC has focused on obtaining geo-environmental parameters such as fluid resistivity and soil engineering properties such as porosity and degree of saturation from measurements of bulk soil electrical resistivity using the empirical relationship proposed by Archie (1942). Within this framework, the paper illustrates and discusses important design and calibration issues for resistivity modules such as the use of isolated circuitry to achieve linear calibrations over large ranges of resistivity. The suitability of RCPTU measurements for determination of geo-environmental and geotechnical parameters are assessed using typical ranges of soil and groundwater properties and methods of isolating individual factors for study are discussed. Illustrative examples of RCPTU research efforts including the environmental characterization of mine tailings, delineation of saline water intrusions in fresh water aquifers and the quality control of geotechnical ground densification are presented throughout the text. It is shown that groundwater temperature and hence ion mobility is not significantly altered by frictional heat generated during piezocone penetration and that ratio-based approaches to monitoring soil porosity can be used to eliminate the requirement for extensive groundwater sampling programs. Lastly, it is shown that RCPTU measurements above the water table can only be made using resistivity modules that are stable over a large range of resistivities and that such measurements are the most difficult to interpret because of grain surface conduction effects and generally unknown fluid resistivities.
Keywords: Electric conductivity; Groundwater; Hydrochloric acid; Land fill; Leachate treatment; Electrical resistivity tomography (ERT); Piezocone penetration tests (CPTU); Reactivation; The University of British Columbia (UBC); Geophysics; geotechnical engineering; soil mechanics